La «invenzione» del carcere, tra carità cristiana e illuminismo penale (secc. XVII-XVIII) - Elio Tavilla (DNA Di Nulla Academia, 2023)
The imprisonment, from mere temporary custody pending the conclusion of the judgment, becomes an autonomous and gradable penalty through the work of the Church in the modern age. A vivid representation of the conditions of the prisons of the Papal States is given by G.B. Scanaroli in his work De visitatione carceratorum (1655), which inspired  L.A. Muratori in his treatises La carità cristiana (1723) and Della pubblica felicità (1749). Finally, the eighteenth-century reformism on the one hand expressed hostility to the cruelty of punishment, including prison (C. Beccaria), for the other conceived forced labor as a “utilitarian” way to exploit the detention of prisoners (J. Bentham).